2011
DOI: 10.1111/j.1747-0285.2011.01130.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacophore Development and Docking Studies of the HIV‐1 Integrase Inhibitors Derived from N‐methylpyrimidones, Dihydroxypyrimidines, and Bicyclic Pyrimidinones

Abstract: To elucidate the crucial structural features for the HIV-1 integrase inhibitors, a three-dimensional pharmacophore model was developed based on N-methyl pyrimidones, dihydroxypyrimidines, and bicyclic pyrimidinones derivatives using Phase. N-methyl pyrimidone derivative raltegravir, the first US-FDA approved drug by Merck, belongs to this series. The best-fitted common pharmacophore hypothesis was characterized by two acceptor, two hydrophobic, and two ring features having a correlation coefficient of 0.895, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Ligand-based drug design approaches like quantitative structure-activity relationship (QSAR) and pharmacophore modeling have established their effectiveness in designing/envisaging the action of new molecules and in searching chemical databases to detect novel lead scaffolds in the absence of target receptor 3D structure [97][98][99]. QSAR and quantitative structure-property relationship approach developed a mathematical model for biological activity employing numerous structural and functional properties [100][101][102].…”
Section: Computer-aided Drug Design/repurposingmentioning
confidence: 99%
“…Ligand-based drug design approaches like quantitative structure-activity relationship (QSAR) and pharmacophore modeling have established their effectiveness in designing/envisaging the action of new molecules and in searching chemical databases to detect novel lead scaffolds in the absence of target receptor 3D structure [97][98][99]. QSAR and quantitative structure-property relationship approach developed a mathematical model for biological activity employing numerous structural and functional properties [100][101][102].…”
Section: Computer-aided Drug Design/repurposingmentioning
confidence: 99%
“…The computational methods in drug discovery collectively termed pharmacoinformatics, includes structure activity relationship (SAR), pharmacophore, virtual screening and molecular docking and these have proven their pivotal role in the pharmaceutical industry for lead identification and optimization. Several research groups worldwide identified integrase inhibitors [11][12][13][14][15][16][17] using pharmacoinformatics approaches for potential application for HIV therapy. Consistent with the objective of developing new potent and less toxic integrase inhibitors the current research explores the binding preferences of the inhibitory molecules of HIV integrase in terms of space modelling study and virtual screening along with molecular docking and molecular dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Integrase (IN), a 32 kDa protein in Human Immunodeficiency Virus (HIV), is a promising anti-HIV target and several classes of inhibitors have been reported (Gupta, Roy & Garg 2009; Plewe et al 2009; Cheng, Zhang & Fu 2010; Tanis et al 2010; Johnson et al 2011; Sharma et al 2011; Telvekar & Patel 2011). IN active-site-directed strand transfer inhibitors, Raltegravir, Elvitegravir and Dolutegravir have been approved by Food and Drug Administration for anti-retroviral therapy (http://aidsinfo.nih.gov/guidelines; Summa et al 2008; Volberding & Deeks 2010).…”
Section: Introductionmentioning
confidence: 99%